Resource Allocation and User Association in Massive MIMO Enabled Wireless Backhaul Network - Rajoria, Shweta; Trivedi, Aditya; Godfrey, W. Wilfred; Pawar, Praveen (IEEE Vehicular Technology Conference, 2019)
Small cell and heterogeneous network are the promising technologies to provide good coverage and throughput and hence, recently attracted attention for the future cellular network. However, backhauling of irregularly located large number of small cells can be a critical issue in its deployment. The paper provides a general framework of massive MIMO backhauling in a heterogeneous network. The architecture consists of full duplex small cells which can receive backhaul data from massive MIMO enabled macro base station and transmit data to its users in the same frequency band. The paper aims at jointly optimizing the sum logarithm rate with respect to user association, number of antennas, and bandwidth allocation, subject to wireless backhaul as a constraint. A mixed integer non-linear programming problem is formulated. To solve the problem efficiently, the primal problem is splitted into three sub-problems and solved individually. Simulation results demonstrate considerable improvement in the performance over the existing results.